2014
DOI: 10.1074/jbc.m114.561878
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Studies of DNA Polymerase β

Abstract: Background: DNA Pol ␤ participates in base excision repair by choosing correct dNTP to fill single-nucleotide gaps in DNA. Results: Pol ␤ experiences a non-covalent step with correct dNTP selection. Conclusion: Correct and incorrect dNTP incorporation by Pol ␤ are different. Significance: FRET-based system of Pol ␤ elucidates a mechanism of substrate choice necessary for understanding the molecular basis of human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 60 publications
9
59
0
Order By: Relevance
“…Such postcatalytic active site rearrangement and protein conformational change are consistent with those projected through kinetic studies. 3639 The pyrophosphate dissociation from the crystals observed here was not seen previously after correct nucleotide incorporation onto undamaged DNA by hPol β in crystallo. 12 Furthermore, 8-oxoG in the nicked DNA product after dCTP incorporation was best modeled in both anti - and syn- conformations (Figure S6A), and the incorporated dCMP had poor electron density and stacked, rather than base paired, with 8-oxoG (Figure 1E).…”
Section: Resultssupporting
confidence: 51%
“…Such postcatalytic active site rearrangement and protein conformational change are consistent with those projected through kinetic studies. 3639 The pyrophosphate dissociation from the crystals observed here was not seen previously after correct nucleotide incorporation onto undamaged DNA by hPol β in crystallo. 12 Furthermore, 8-oxoG in the nicked DNA product after dCTP incorporation was best modeled in both anti - and syn- conformations (Figure S6A), and the incorporated dCMP had poor electron density and stacked, rather than base paired, with 8-oxoG (Figure 1E).…”
Section: Resultssupporting
confidence: 51%
“…39 To increase specificity and fidelity, pol β utilizes multiple kinetic steps to govern substrate selection. 32,4042 Previous evidence indicates that, for pol β, chemistry is normally rate-determining for both correct and incorrect nucleotides, though the activation energy barrier for the forward reaction of the incorrect dNTP is much higher. 40,4246 It has been suggested that the difference in energy results from a distorted active site in the presence of a mismatch.…”
mentioning
confidence: 99%
“…32,40,42 Conformational changes occur upon binding of the correct dNTP, which result in closing of the fingers subdomain and other smaller movements that align the active site for an inline nucleophilic attack with the incoming dNTP, as shown by structural and FRET studies. 1315,32,33 This then commits the enzyme to chemistry particularly if the reverse fingers opening is a slow reaction compared to the rate of chemistry. 34,35 The chemical reaction requires deprotonation of the 3′-OH to assist with the nucleophilic attack of the 3′-oxygen on Pα of the bound dNTP.…”
mentioning
confidence: 99%
“…Crystal structures with open (Figure 5d), closed (Figure 5e), and intermediate conformations have been obtained with mismatched or incorrect dNTPs, such as dA that cannot form a correct base pair with dG of the DNA substrate. Previous fluorescence studies [118,121,122] showed movements in Pol β upon incorporation of dNTPs and cofactors, while more recent studies [108] indicate the rapid movement (ms timescale) of the fingers domain upon binding to correct dNTPs. Incorporation of incorrect dNTPs did not induce these conformational changes.…”
Section: Case Studiesmentioning
confidence: 99%
“…The chemical step of catalysis is followed by the release of pyrophosphate (PP i ) and the DNA product (DNA n +1 ) (step 4). Figure adapted from [108,109]. …”
Section: Figurementioning
confidence: 99%